Antifungal activity of probiotics and their metabolites and elucidation of the mechanism of interaction - Pant, Krisha; Anal, Anil Kumar; Loc Thai Nguyen; Datta, Avishek; Bangchak Petroleum Public Company Limited, Thailand (Pathum Thani, Thailand : Asian Institute of Technology, 2021)
Food contamination by Aspergillus and the toxic metabolites produced by them have been known to cause food safety issues and has been recently countered by biocontrol methods using Lactobacillus. This study was carried out to evaluate the inhibitory interaction between fungi Aspergillus niger and live Lactobacillus cell and elucidate the antifungal mechanism of action by partially purified Lactobacillus extract. Further, the applicability of these extract with chitosan was observed in table grapes and chicken patties in-terms of coatings and antimicrobial films respectively. There was significant reduction in the viability (1 log reduction) and biomass (55.15%) of fungi by both Lactobacillus cells. The mechanism of inhibitory action by L. casei was found to be by increasing the permeance of cell wall of fungi by interaction with the cell wall and cell membranes by the process of cell leakage from fungi causing changes in the morphology like hollowing/flattening of hyphae, visualized through SEM. In contrast to that, Lactobacillus plantarum was found to inhibit fungal cell growth by mechanism other than interaction with both cell wall and cell membrane as observed through sorbitol and ergosterol assay. Strong antifungal activities of L. casei extract with chitosan were detected as coating (3 log reduction) and films (2.84 log reduction) in both grapes and chicken respectively due to synergistic antifungal action FICindex (<1) by the hydrogen bonding and electrostatic interaction observed by FTIR analysis. Addition of antifungal extract from L. casei was found to disrupt the bonding between and within the the long chain chitosan molecules in the film, changing its mechanical properties (tensile stress (MPa), elongation at break, EB%) and making it more susceptible to water permeability, increased thickness, swelling index. This susceptibility was encountered by crosslinking the chitosan by phosphate salts.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Food Engineering and Bioprocess Technology, School of Environment, Resources and Development
Thesis (M. Eng.) - Asian Institute of Technology, 2021
Keywords: Probiotics; Metabolites; Chitosan -- Biotechnology